2016
DOI: 10.1186/s11671-016-1671-7
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Rashba/Dresselhaus Spin Splittings by Inserting Ultra-Thin InAs Layers at Interfaces in Insulating GaAs/AlGaAs Quantum Wells

Abstract: The ratio of Rashba and Dresselhaus spin splittings of the (001)-grown GaAs/AlGaAs quantum wells (QWs), investigated by the spin photocurrent spectra induced by circular photogalvanic effect (CPGE) at inter-band excitation, has been effectively tuned by changing the well width of QWs and by inserting a one-monolayer-thick InAs layer at interfaces of GaAs/AlGaAs QWs. Reflectance difference spectroscopy (RDS) is also employed to study the interface asymmetry of the QWs, whose results are in good agreement with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…where m is the band effective mass, α is the Rashba coefficient, σ = (σ x , σ y , σ z ) is the vector of Pauli matrices, k = (k x , k y ) is the in-plane wavevector, and ẑ is a unit vector along the z direction. It is possible to include the Dresselhaus spin-orbit coupling [44], but it is not the focus of this paper. There are two spin-split bands: the upper band with energy ε k+ and the lower band with energy ε k− , where ε k± = 2 k 2 /2m ± αk and k = |k|.…”
Section: A Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation
“…where m is the band effective mass, α is the Rashba coefficient, σ = (σ x , σ y , σ z ) is the vector of Pauli matrices, k = (k x , k y ) is the in-plane wavevector, and ẑ is a unit vector along the z direction. It is possible to include the Dresselhaus spin-orbit coupling [44], but it is not the focus of this paper. There are two spin-split bands: the upper band with energy ε k+ and the lower band with energy ε k− , where ε k± = 2 k 2 /2m ± αk and k = |k|.…”
Section: A Hamiltonianmentioning
confidence: 99%
“…It is therefore natural to expect systems that have strong electronelectron interactions as well as strong spin-orbit coupling to exhibit a multitude of exotic, unconventional states of matter. In light of this, the fascinating interplay of spin-orbit coupling and electron-electron interactions has received considerable attention in recent years, in materials ranging from topological insulators to conventional semiconductors [34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that when measuring the CPGE current, the light spot is located at the midpoint of the connection of the two contacts, where the PISHE is zero according to [ 20 ]. The CPGE current is also normalized by the corresponding photocurrent under a bias of 0.3 V to eliminate the influence of the carrier mobility and the carrier density in different crystal directions [ 51 ]. Then, we use the following equation to fit the normalized angle-dependent CPGE current to obtain the relative SOC strength along different crystal directions [ 21 , 27 ]:
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…When the incident plane of light lies in [1 0] direction and the CPGE current is collected along [110] direction, the corresponding A parameter, denoted as A [110] , is proportional to the sum of Rashba and Dresselhaus SOC, i.e., A [110] ∝ α + β [ 51 53 ]. When the incident plane of light lies in [010] direction and the CPGE current is collected along [100] direction, the corresponding A parameter, denoted as A [100] , is proportional to the Rashba SOC, i.e., A [100] ∝ α [ 51 53 ]. Thus, by the ratio of A [110] / A [100] , we can get the relative ratio of Rashba to Dresselhaus SOC, i.e., = 0.32, which indicates that the spin splitting in the GaAs/AlGaAs 2DEG has crystal anisotropy [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…7 The Rashba 8 and the Dresselhaus 9 SOC terms, present due to the surface or bulk inversion asymmetry, respectively, lead in turn to the DMI, which is the subject of this paper. Recently experimenters 6,7,[10][11][12][13] have been able to tune the strength of the DMI, using quantum well structures and/or gate voltage, which would lead in turn to the tuning of the magnetic exchange interactions between neighboring spins. Interestingly, Chen et al have shown that by tuning the DMI, the chirality of the magnetic domain walls can be altered.…”
Section: Introductionmentioning
confidence: 99%